The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.2139/ssrn.1587978
|View full text |Cite
|
Sign up to set email alerts
|

Global Production Networks in Electronics and Intra-Asian Trade

Abstract: The growth of East Asia's intra-regional trade is driven largely by increased component trade within global electronics production networks. Data on both electronics trade and production elucidate a pattern of specialization in which upper-and middle-income countries produce sophisticated components and lower-income countries assemble lowervalue-added final goods. There is evidence of increasing sophistication within the electronics sector by the Newly Industrialized Economies and to a lesser extent by ASEAN c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Third, the progressive integration of China with the regional and global production networks during the 1990s, and its leap after accessing the WTO in 2001, induced a whole new wave and dimension of outsourcing and production relocation to the country, which reverberated across the entire region and the world economy (Gangnes, ).…”
Section: Vertical Trade Mapsmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, the progressive integration of China with the regional and global production networks during the 1990s, and its leap after accessing the WTO in 2001, induced a whole new wave and dimension of outsourcing and production relocation to the country, which reverberated across the entire region and the world economy (Gangnes, ).…”
Section: Vertical Trade Mapsmentioning
confidence: 99%
“…Third, the progressive integration of China with the regional and global production networks during the 1990s, and its leap after accessing the WTO in 2001, induced a whole new wave and dimension of outsourcing and production relocation to the country, which reverberated across the entire region and the world economy (Gangnes, 2010). Fourth, the rapid expansion of global demand for consumer goods in the period leading up to the 2008-2009 global financial crisis spurred growth, especially in the highly fragmented industries, such as electronics in East Asia.…”
Section: Iv2 the Rise Of China As A Global Hub During The 2000smentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that manufacturing development foster greater external integration with the world through trade and investment (Gangnes and Assche 2010). However, efforts to deepen manufacturing development have not succeeded in nurturing a critical mass of domestic entrepreneurs with indigenous innovative capacities that can move Malaysia up the value chain of production.…”
Section: Introductionmentioning
confidence: 99%